Unravelling the Lineus ruber/viridis species complex (Nemertea, Heteronemertea). (21st June 2016) - Krämer, Daria; Schmidt, Christian; Podsiadlowski, Lars; Beckers, Patrick; Horn, Lisa; von Döhren, Jörn
Abstract : Lineus ruber (Müller, 1774 ) and Lineus viridis (Müller, 1774 ) are among the longest known and most abundant intertidal nemertean species found on both sides of the North Atlantic. Due to easy maintenance in captivity, both species have been well studied concerning morphology, reproduction, development and ecology. Originally described as two separate species in the 18th century, they were subsequently synonymised and considered colour varieties of a single species. It was not until the mid‐20th century that complementary redescriptions, including information on reproduction and development, re‐established the specific identities of L. ruber and L. viridis . With the advent of molecular markers in nemertean systematics, however, doubt was again cast on their specific identities. To solve one of the longest standing problems in nemertean systematics, we assembled a comprehensive data set combining external morphology and three genetic markers (mitochondrial cytochrome c oxidase subunit I, 16S rRNA and nuclear internal transcribed spacer region) from 160 specimens of L. ruber and L. viridis collected at six sampling sites along the continental coast of Western Europe. The data set was analysed with tree‐based and non‐tree‐based species delimitation methods. The results from all methods used confidently delimit three separate clades. A distinct barcoding gap was detected in our data set which thus provides a framework to unequivocally identify specimens as members of any of the three species. Comparison of our findings with published data enables us to assign one lineage to L. ruber and one to L. viridis . We designated neotypes for both species. The third clade is very similar to L. viridis, only distinguishable by a conspicuous, iridescent ventral fold in some male specimens This lineage shows a syntopic distribution along western European coasts and represents a species new to science and is described as Lineus clandestinus sp. n. based on its external characters and the analyses of the molecular data provided in this study.